Philippine policy reforms and infrastructure development a historical account - Canlas, Dante B. (The Philippine Review of Business and Economics, 2017)
Following the restoration of democratic political institutions in 1986, the Philippine government, under a succession of political administrations, has pursued a structural policy reform program on several fronts, both economic and non-economic. This paper assesses some policy reforms in the government's infrastructure development program and the institutional arrangements aimed at implementing such reforms. Some progress has been achieved under the leadership of the National Economic and Development Authority and oversight of the various inter-agency NEDA Board committees, such as the infrastructure, investment coordination, and development budget coordination committees. The enactment of the Build-Operate-Transfer Law, for instance, has broadened and deepened the participation of the private sector in the infrastructure program. At this juncture, however, closing the infrastructure gap, particularly in transport, continues to be a formidable challenge. Major improvements, among other concerns, in procurement and implementation capacities of implementing government agencies, fair allocation of public-private risk bearing in contracts, and elimination of corruption in the approval process at all levels of government, national and local, are indicated.